New coil configurations with 2G-HTS and benefits for applications. (19th August 2021) - Arndt, Tabea; Holzapfel, Bernhard; Noe, Mathias; Nast, Rainer; Hornung, Frank; Kläser, Marion; Kudymow, Andrej
Abstract: A scalable concept to prepare high current density windings with high-temperature superconducting material is introduced. The concept covers miniaturized high-current windings and large coils for applications in energy technology as well. The principle is based on a circular disk-up-down-assembly ('DUDA') and extended to rectangular coils. First measurements on the assemblies (≍40 turns) in liquid nitrogen are presented as a proof-of-concept. Centre fields of ≍40 mT and ≍340 mT are measured during steady operation and pulsed operation respectively. Operating the assemblies at lower temperatures will strongly increase the current and field performance. Lowering the contact resistance might lead to further improvements. Due to the homogenous structure in the radial direction, shear stresses are minimized and large winding heights can be realized in principle. The DUDA concept of coil windings can be used to build even more sophisticated magnetic arrangements, e.g. Halbach-arrays, or complex windings for new stator configurations of rotating machines. The optional miniaturization offers compact and powerful magnets, e.g. for accelerators too.